A HINDU ENCOUNTERS CHRIST - Saldanha, Julian (Asian Horizons, 2011)
It is well known that the life and teaching of Christ have exerted an enormous influence on Hindus in India. In fact, if the divine Word/Logos has been in communication with the human race from the beginning, we should expect that when people are presented with this Word become man, they would spontaneously “recognise” him and acknowledge in him the response to their deepest desires, their “seeking expectation”.1 This a priori postulate is confirmed a posteriori by the positive response which non-Christians have given and continue to give to the person and teaching of Christ. Among these we must count Mangesh Padgaonkar, a well-known Marathi writer, born in 1929. He is a poet and essayist, with about forty publications to his credit. Besides receiving the Sahitya Akademi Award in 1980, he has been given several literary awards in Maharashtra. He has recently published his own Marathi translation of the four Gospels, prefaced with his insightful reflections (in Marathi) on each of the Gospels: Bible: Navā Karār (“Bible: the New Testament”), Mauz Prakashan, Mumbai, 2008. The Beatitudes in Matthew and Luke stirred his poetic talent to translate them into attractive verse form. His reflections on Matthew’s Gospel cover more space than those on the other three Gospels combined; no reason is adduced for this. An introduction traces the origins of Bible translations into the vernaculars. His interest in the Bible began as a student in the English medium Wilson School, run by the Church of North India in Mumbai. Here there were regular, rather boring, classes on the New Testament. It was only in his final year in school that he came into possession of an English translation of the New Testament. He found the cadences of that translation so much like those of Tagore’s English version of his Gitānjali that it caught his fancy as a budding poet. Here lay the origins of his desire to make a Marathi translation of his own.